ТРАНСФОРМАЦІЙНІ ПРОЦЕСИ СУЧАСНОСТІ ТА ЇХ ВПЛИВ НА ДЕРЖАВНО-ПРАВОВУ ДІЙСНІСТЬ УКРАЇНИ - Пампура, Максим Валерійович (SUPREMANCE OF LAW, 2016)
The main directions of transformational processes in modern world are offered. The content and specific features of the contemporary world’s transformational processes are considered. The interrelation of the world’s transformational process and democratic modernization processes in Ukraine is analyzed. The priorities of Ukraine in international political relations are offered.